2021
DOI: 10.3389/fphar.2021.717757
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Based on Molecular Docking and Molecular Dynamics Simulation Study of Bromelain as Anti-SARS-CoV-2 Variants

Abstract: The rapid spread of a novel coronavirus known as SARS-CoV-2 has compelled the entire world to seek ways to weaken this virus, prevent its spread and also eliminate it. However, no drug has been approved to treat COVID-19. Furthermore, the receptor-binding domain (RBD) on this viral spike protein, as well as several other important parts of this virus, have recently undergone mutations, resulting in new virus variants. While no treatment is currently available, a naturally derived molecule with known antiviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Tallei et al [229], for the first time, applied molecular docking and molecular dynamics simulation approaches to investigate the ability of bromelain to counteract various variants of the SARS-CoV-2 by targeting bromelain binding on the side of this viral interaction with angiotensin converting enzyme 2 (ACE2). The researchers found that bromelain exhibited good binding affinity toward various variants of the receptor-binding domain (RBD) responsible for the attachment of the virus to ACE2.…”
Section: Possible Management Of Bromelain In Covid-19 Disease Treatmentmentioning
confidence: 99%
“…Tallei et al [229], for the first time, applied molecular docking and molecular dynamics simulation approaches to investigate the ability of bromelain to counteract various variants of the SARS-CoV-2 by targeting bromelain binding on the side of this viral interaction with angiotensin converting enzyme 2 (ACE2). The researchers found that bromelain exhibited good binding affinity toward various variants of the receptor-binding domain (RBD) responsible for the attachment of the virus to ACE2.…”
Section: Possible Management Of Bromelain In Covid-19 Disease Treatmentmentioning
confidence: 99%
“…When compared to bromelain, the binding position of bromelain-derived peptide is generally similar, namely at the hACE2-RBD binding site. This is demonstrated by the similarity of the interacting amino acids between RBD WT and variants and these two molecules, particularly the critical residues Phe486, Gln493, and Asn501 [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous in silico research, bromelain has a high binding affinity for various RBD variants and binds directly at the binding site between RBDs and hACE2. This suggests that bromelain has the potential to inhibit SARS-CoV-2 attachment to hACE2 [ 27 ]. In one study, the bromelain peptide biomarker DYGAVNEVK was found in the plasma of bromelain-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…BromAc also induced the unfolding of recombinant spike and envelope proteins by reducing disulfide stabilizer bridges and inhibited the replication of wild-type and spike mutant SARS-CoV-2 (Akhter et al, 2021). Moreover, in an in silico study, Tallei et al (2021) suggests that bromelain effectively binds to receptor-binding domain (RBD)'s active site of spike glycoprotein and also could have an inhibitory effect on different SARS-CoV-2 variants. This result is encouraging, given the number of SARS-CoV-2 variants that have been identified.…”
Section: Sagar Et Al (2021) Demonstrated That Bromelain Can Inhibit Sars-mentioning
confidence: 99%
“…The proteinases found in pineapple include fruit bromelain (EC 3.4.22.33), stem bromelain (EC 3.4.22.32),and ananain (EC 3.4.22.31). Bromelain has proven therapeutic properties, for example, antiinflammatory, anticoagulant, anthelminthic, antimicrobial, and immunomodulatory effects (Chakraborty et al, 2021;Kritis, Karampela, Kokoris, & Dalamaga, 2020;Tallei et al, 2021). Here, we will emphasize its antiviral effect, particularly anti-SARS-CoV-2.…”
mentioning
confidence: 99%